Workers' biomechanical loads and kinematics during multiple-task manual material handling. (February 2020) - Harari, Yaar; Bechar, Avital; Riemer, Raziel
Abstract: This study investigated the biomechanical loads and kinematics of workers during multiple-task manual material handling (MMH) jobs, and developed prediction models for the moments acting on a worker's body and their peak joint angles. An experiment was conducted in which 20 subjects performed a total of 3780 repetitions of a box-conveying task. This task included continuous sequential removing, carrying and depositing of boxes weighing 2–12 kg. The subjects' motion was captured using motion-capture technology. The origin/destination height was the most influencing predictor of the spinal and shoulder moments and the peak trunk, shoulder and knee angles. The relationship between the origin/destination heights and the above parameters was nonlinear. The mass of the box, and the subject's height and mass, also influenced the spinal and shoulder moments. A tradeoff between the moments acting on the L5/S1 vertebrae and on the shoulder joint was found. Compared to the models developed in similar studies that focused on manual material handling (albeit under different conditions), the high-order prediction equation for peak spinal moment formulated in the present study was found to explain between 10% and 48% more variability in the moments. This suggests that using a high-order equation in future studies might improve the prediction. Highlights: 20 subjects performed 3780 repetitions of continuous sequential box conveying task. Handled boxes weighted from 2 to 12 kg and shelves heights from 20 to 170 cm above floor. Prediction models were developed for spinal and shoulder moments and joint angles. Shelf height was main predictor of moments and angles with a nonlinear relationship. Changes in shelf height resulted in a tradeoff between spinal and shoulder moments.